Maslahah Sebagai Alternatif Istinbath Hukum Dalam Ekonomi Syari’ah - Moh Syarifuddin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2018)
The scholars throughout history always put maslahah as the main principle in shari'ah. The purpose or intent of the shari'ah or the contemplation of Islamic law is to preserve religion, to preserve the soul, to preserve wealth, to preserve the intellect, and to preserve the offspring which all propagate to human welfare. Therefore, maslahah is the purpose of the Islamic shari'a. However, the benefits that were initially the main goals of Islamic law, have not yet fully implemented. This article will discuss about Maslahah in his affiliation with how his opportunities are used as one of the alternative legal provisions in the Shari'a Economics. Creating benefits is the purpose of shari'ah, the desired benefits of the world and the hereafter. To measure the benefits must be seen from the level of human needs ie the needs of daruryy, hajiyyat, and tahsiniyyat. The concept of goodwill will make a great contribution when implemented in shari'ah economic development. That is, in the concept of fulfilling human needs, paradigm of economic activity (production, consumption, and distribution), and utility standards